Collagen chirality and three‐dimensional orientation studied with polarimetric second‐harmonic generation microscopy. Issue 1 (14th October 2018) - Golaraei, Ahmad; Mirsanaye, Kamdin; Ro, Yeji; Krouglov, Serguei; Akens, Margarete K.; Wilson, Brian C.; Barzda, Virginijus
Abstract : Polarization‐dependent second‐harmonic generation (P‐SHG) microscopy is used to characterize molecular nonlinear optical properties of collagen and determine a three‐dimensional (3D) orientation map of collagen fibers within a pig tendon. C6 symmetry is used to determine the nonlinear susceptibility tensor components ratios in the molecular frame of reference χ zzz 2 / χ zxx 2 and χ xyz 2 / χ zxx 2, where the latter is a newly extracted parameter from the P‐SHG images and is related to the chiral structure of collagen. The χ xyz 2 / χ zxx 2 is observed for collagen fibers tilted out of the image plane, and can have positive or negative values, revealing the relative polarity of collagen fibers within the tissue. The P‐SHG imaging was performed using a linear polarization‐in polarization‐out (PIPO) method on thin sections of pig tendon cut at different angles. The nonlinear chiral properties of collagen can be used to construct the 3D organization of collagen in the tissue and determine the orientation‐independent molecular susceptibility ratios of collagen fibers in the molecular frame of reference. Abstract : Chirality of collagen is studied in a tendon tissue using a polarimetric second‐harmonic generation microscopy technique. A three‐dimensional (3D) orientation and the relative polarity of neighboring fibers are revealed. This information can be utilized for 3D reconstruction of collagen organization, which aid scientists in better understanding of the architecture and function of the collagen‐based tissues.